Improving the generalizability of infant psychological research: The ManyBabies model. (10th February 2022) - Visser, Ingmar; Bergmann, Christina; Byers-Heinlein, Krista; Dal Ben, Rodrigo; Duch, Wlodzislaw; Forbes, Samuel; Franchin, Laura; Frank, Michael C.; Geraci, Alessandra; Hamlin, J. Kiley; Kaldy, Zsuzsa; Kulke, Louisa; et al.
Abstract: Yarkoni's analysis clearly articulates a number of concerns limiting the generalizability and explanatory power of psychological findings, many of which are compounded in infancy research. ManyBabies addresses these concerns via a radically collaborative, large-scale and open approach to research that is grounded in theory-building, committed to diversification, and focused on understanding sources of variation.